INITIAL GROWTH OF COFFEE AND FERTILITY OInitial growth of coffee and fertility of soil fertilized with mucuna, pinto peanut (Arachis Pintoi) or ammonium sulphate - Ferreira Vilela, Emerson; Regina Carvalho Freitas, Monique; Branco Piano, Patrícia; Silva Santos, Ricardo Henrique; de Sá Mendonça, Eduardo (Coffee Science - ISSN 1984-3909, 2011)
Coffee plants have high nutrient demand and the growing demand for raw materials of biological origin for agricultural production and renewable and green manure can contribute to nutrition of the trees. However, while studies of green manure in coffee have focused on the N ,Fabaceaes also accumulate other nutrients. The objective of this study was to evaluate the effect of supplying other nutrients besides N to Fabaceaes in the initial growth of coffee plants (Coffea arabica L.) and on soil fertility. The study was conducted from 10/01/2007 to 09/01/2008 in Viçosa, MG. The treatments consisted of fertilization with ammonium sulfate, mass of mucuna (Mucuna pruriens (L.) DC.) or pinto peanut (Arachis pintoi Krapov. & WC Gregory). The seedling growth was measured monthly as to plant height, stem girth, total number of leaves, total number of branches, total number of nodes and canopy diameter. Soil fertility was assessed by routine analysis at the end of the experiment. The differences were expressed from the fourth month after planting. The coffee plants that received fertilization with fabaceous mulch showed higher vegetative growth than those receiving only ammonium sulfate, with the exception of plant height. Soil mixed with mulch of any of the Fabaceaes showed higher pH and higher contents of P, K and, values of SB, effective CTC, V and P-rem than those that received only ammonium sulphate. Soils fertilized with fabaceaes presented a higher fertility than soils fertilized with ammonium sulfate, despite the increase in coffee tree growth.